Global social cleansing: postliberal revanchism and the export of zero tolerance - Smith, Neil (Social justice, 2001)
The globalization of zero tolerance law enforcement has occurred with the speed of light, which is a response to deeply ingrained and broadly parallel insecurities that range across several continents. In New York City, zero tolerance policing has fueled race and class profiling that encourages high numbers of street arrests, with concerns about evidence being minimized. The danger is that the New York model could become the guideline for a liberal and global revanchism that could inflict revenge against different social groups in various places, doing so with different levels of intensity and adopting quite varied forms.